Ambivalences of Creating Life Societal and Philosophical Dimensions of Synthetic Biology - Hagen, Kristin; Engelhard, Margret; Toepfer, Georg (Ethics of Science and Technology Assessment, 2016)
"Synthetic biology" is the label of a new technoscientific field with many different facets and agendas. One common aim is to "create life", primarily by using engineering principles to design and modify biological systems for human use. In a wider context, the topic has become one of the big cases in the legitimization processes associated with the political agenda to solve global problems with the aid of (bio-)technological innovation. Conceptual-level and meta-level analyses are needed: we should sort out conceptual ambiguities to agree on what we talk about, and we need to spell out agendas to see the disagreements clearly. The book is based on the interdisciplinary summer school "Analyzing the societal dimensions of synthetic biology", which took place in Berlin in September 2014. The contributions address controversial discussions around the philosophical examination, public perception, moral evaluation and governance of synthetic biology.